Fatigue Reliability in Uniaxial State of Stress Produced by Synchronous Loads - Kolenda, J. (Engineering Transactions, 1993)
The paper deals with the stress-based fatigue analysis of structural members subjected to synchronous and in-phase loads. The uniaxial state of stress produced by combined bending and tension-compression is considered. Attention is focused on the failure subregion for high cycle fatigue where the linear logarithmic models for fatigue behaviour are applicable. The relationships for calculation of fatigue reliability and number of cycles to failure are proposed. For the assessment of the probability of fatigue failure under the stress with normally distributed amplitudes of its components, the reliability index is determined.